Towards Content Neutrality in Wiki Systems - Clemens H. Cap (Future Internet, 2012)
The neutral point of view (NPOV) cornerstone of Wikipedia (WP) is challenged for next generation knowledge bases. A case is presented for content neutrality as a new, every point of view (EPOV) guiding principle. The architectural implications of content neutrality are discussed and translated into novel concepts of Wiki architectures. Guidelines for implementing this architecture are presented. Although NPOV is criticized, the contribution avoids ideological controversy and focuses on the benefits of the novel approach.